The Influence of Narcotics and Illegal Drugs in Society: Facts and Efforts for Prevention - Langi, Marsil Tangke; Qalbi, Vivi Nur; Lestari, Titie Yustisia (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
This article aims to analyze the phenomenology of narcotics and illegal drug abuse in society. This study uses a qualitative method with content analysis. The research was conducted in an area in South Sulawesi, Indonesia, focusing on trends in narcotics abuse and countermeasures taken by the police. Data was obtained from the analysis of 15 official documents, such as annual police reports, data on narcotics abuse cases from 2018 to 2023, and narcotics handling policies. The analysis tool used was a thematic categorization table to group data based on case patterns and the forms of intervention carried out. The data analysis technique used was content analysis with a descriptive-qualitative approach. The results of the study show an increase in the number of cases in 2019 (49 cases), 2022 (45 cases), and 2023 (60 cases). Countermeasures were carried out through pre-emptive (education and guidance), preventive (routine operations in vulnerable locations), and repressive (law enforcement against perpetrators) strategies. This study emphasizes the importance of community involvement and cross-sectoral synergy to prevent and combat drug abuse in a sustainable manner.